Edubox Utilization as Tool For Evaluation of Learning Outcomes Social Studies - Ambarwati, Inggar Carissa; Komalasari, Kokom; Effendi, Ridwan (International Journal Pedagogy of Social Studies, 2019)
This research discusses about E-Learning, which is needed to balancedÂ  Education in this modern era. There is a difference in the implementation of E-Learning in every school, what the researchers found is the evaluation system to get the results of learning the value of knowledge that is done online by using an application called Edubox. This research aimed :(1) To know the studentâ€™s response to Edubox utilization as an evaluation tool in SMP Negeri 10 Bandung. (2) To know effective IPS learning outcomes of students after using Edubox class VII SMP Negeri 10 Bandung. (3) To Know the results of the cognitive Social Studies learning of students after using Edubox in class VII SMP Negeri 10 Bandung. This research used qualitative descriptive study methods. The participant of this research is 7 random students in every class, Social Studies teachers and vice-principal as the facilities and infrastructures in the field of management Edubox. The Data collecties by interviews, observations, and documentation, while analyzing data using data reduction, data presentation, data verification. The finding shows that 1) the response of the learner, educators, schools on the existence of Edubox brought a positive impact so that the evaluation can be implemented easily. 2) Edubox presence provide change to students in affective learning outcomes such as attitudes, interests and better self-concepts. 3) Edubox can make the learning results in the form of the knowledge value of the learners increased from the previous results. Therefore, I used Edubox as Social Studied learning outcome tool.